Electromagnetic energy harvesting based on HfZrO tunneling junctions. (31st August 2018) - Dragoman, Mircea; Modreanu, Mircea; Povey, Ian M; Aldrigo, Martino; Dinescu, Adrian; Dragoman, Daniela
Abstract: HfZrO ferroelectrics with a thickness of 6 nm were grown directly on Si using atomic layer deposition, top and bottom metallic electrodes being subsequently deposited by electron-beam metallization techniques. Depending on the polarity of the ±10 V poling voltages, the current–voltage dependence of these tunneling diodes shows a rectifying behavior for different polarizations, the ON–OFF ratio being about 10 4 . Because the currents are at mA level, the HfZrO tunneling diodes coupled to an antenna array can harvest electromagnetic energy at 26 GHz (a bandwidth designated for internet of things), with a responsivity of 63 V W −1 and a NEP of 4 nW/Hz 0.5 .